Tan Jin Sing dan komunitas Tionghoa di Yogyakarta Awal Abad KE-19 - Setiawan, Nanang; Fathoni, Rifai Shodiq (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
This research aims to explore Tan Jing Sing's role in determining the direction of Chinese-Javanese relations in Yogyakarta. The historiography of the Yogyakarta Sultanate has been dominated by narratives that describe the roles of Javanese nobles, while the Chinese community only receives a minimal portion of the historiography. This research is expected to fill the gap in the existing historiography so that it can further illustrate the relationship between this community and the Sultanate of Yogyakarta. This research uses the historical method, which includes heuristics, source criticism, interpretation, and historiography, focusing on Tan Jin Sin and the Chinese community in Yogyakarta in the early 19th century. The results show that the conflict between Sultan Sepuh and Crown Prince Raden Mas Surojo was the main cause of Tan Jin Sing's entry into Yogyakarta's political sphere. Tan Jin Sing's involvement in the turmoil was like a double-edged sword. On the one hand, the conflict benefited the Chinese community in Yogyakarta as their economic and political position became more prominent. However, on the other hand, their lives became unsettled as social jealousy arose, leading to the anti-Chinese sentiment among the community.